DNA damage in BV‐2 cells: An important supplement to the neurotoxicity of CdTe quantum dots. Issue 3 (4th December 2018) - He, Keyu; Liang, Xue; Wei, Tingting; Liu, Na; Wang, Yan; Zou, Linyue; Lu, Jie; Yao, Ying; Kong, Lu; Zhang, Ting; Xue, Yuying; Wu, Tianshu; et al.
Abstract: Microglial cells are resident immune cells in the central nervous system. Activation of microglia as induced by CdTe quantum dots (QDs) can trigger damage to neurons. To quantify the intracellular QDs, we monitored the intracellular Cd concentration in the QD‐exposed mouse microglial cells (BV‐2 cell line). The extent of cell injury at different times correlated with the Cd concentration in cells at that time. In addition to Cd ion detection, we also monitored the intracellular fluorescence of the QDs. More QDs accumulated in the nucleus than in the cytoplasm. Comet assays confirmed that QDs induce DNA damage. However, DNA cannot interact with QDs, so the DNA damage was not caused by CdTe QDs adducts to DNA but by the increase of the Cd ion concentration and the secondary oxidative damage. In addition to DNA damage, biofilm injury and endogenous reduced glutathione depletion were also apparent in QD‐exposed BV‐2 cells. These changes can be prevented or even reversed by exogenous reduced glutathione administration. Abstract : DNA damage, biofilm injury and endogenous glutathione depletion in quantum dot‐exposed BV‐2 cells were related to the increasing concentration of Cd ion and reactive oxygen species. These damages can be prevented or even reversed by exogenous glutathione administration.